The Effects of Attendance on Student Learning in Principles of Economics - Durden, Garey C.; Ellis, Larry V. (American Economic Review, 2007)
Does attendance affect performance in college economics courses? David Romer (1993) found that attendance did contribute significantly to the academic performance of students in a large intermediate macroeconomics course that he taught in the fall of 1990. (See the Summer 1994, Journal of Economic Perspectives [vol. 8, no. 3, pp. 205-15] for numerous comments on Romer.) This conclusion held even after controlling for student motivation which, it may be argued, is the true factor determining performance and is only approximated by attendance. An earlier study by Kang Park and Peter Kerr (1990) found that attendance was a determinant of student performance in a money and banking course, but not as important as a student's GPA and the percentile rank on a college entrance exam. A study by Robert Schmidt (1983) reported that time spent attending lectures contributed positively to performance in a macroeconomic Principles course. On the other side of the ledger is evidence from Neil Browne et al. (1991) showing that students who did not attend a typically structured class with lectures did just as well on the Test of Understanding College Economics (TUCE) as those students who attended a standard microeconomic Principles course. They also reported, however, that those students who attended the lectures performed better on essay questions than those who did not. A similar study by Campbell McConnell and C. Lamphear (1969) found no significant difference in the performance of students with no classroom attendance vis-a-vis those attending class. Finally, Stephen Buckles and M. E. McMahon (1971) found attendance at lectures that simply explained material covered in reading assignments did not enhance students' understanding of economics. In this paper we present new evidence on the effects of class attendance on student performance. Our results pertain to the Principles of Economics course as it is taught in a two-semester sequence at a medium-size, comprehensive state university.